Jurisprudencia interamericana sobre desaparición forzada y mujeres : la tímida e inconsistente aparición de la perspectiva de género - Dulitzky, Ariel (2015)
The aim of this article will be to analyze critically the jurisprudence from the Inter-American Court of Human Rights, regarding the cases of forced disappearance, within the doctrine elaborated by the United Nation's involuntary or forced disappearance working group, as to delineate the way in which the issues regarding gender, cross the different aspects of forced disappearance, in cases where women are disappeared and where women are victims of the forced disappearance of their family members